You Never Can Tell - Shaw, Bernard, 1856-1950 (Salt Lake City, UT : Project Gutenberg, 2000)
"You Never Can Tell" by George Bernard Shaw is a four-act play written in 1897. Mrs. Clandon returns to England with her three children after eighteen years abroad, but the children have no idea who their father is. Through a comedy of errors, they end up inviting him to a family lunch. Meanwhile, a dentist named Valentine falls for Gloria, the eldest daughter who claims to have no interest in love or marriage. A wise waiter dispenses advice with the play's titular phrase as identities become confused and comic situations unfold. (This is an automatically generated summary.)
Wikipedia page about this book: https://en.wikipedia.org/wiki/You_Never_Can_Tell_(play)
Release date is 2000-05-01
Produced by An Anonymous Volunteeer and David Widger
Keywords: Comedy plays; England -- Drama; Runaway husbands -- Drama; Wives -- Drama; Fathers -- Drama; Children -- Drama